2020
DOI: 10.1016/j.resourpol.2020.101620
|View full text |Cite
|
Sign up to set email alerts
|

Financialisation of natural resources & instability caused by risk transfer in commodity markets

Abstract: Understanding the connectedness of financial markets and hence possible sources of systematic risk is central to the debate on the process of financialisation and its consequences for financial stability. In this study, we examine the connectedness between commodity spot and futures prices by applying a novel frequency connectedness framework on data from January 1979 to December 2019 to measure the connectedness among financial variables. Focusing on the seven most widely traded commodities, including gold, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 93 publications
1
25
0
Order By: Relevance
“…(2017) who suggested that gold is neither a hedge nor a safe haven asset for stocks in BRIC markets. This result is not surprising because the accelerated financialization of commodity markets ( Huynh et al., 2020b ), including the gold market, has significantly increased investments in gold, making the gold asset behave more and more like stocks. Our findings are contrary to Wen and Cheng (2018) as they argued that safe haven properties of gold for emerging stock markets exist.…”
Section: Resultsmentioning
confidence: 99%
“…(2017) who suggested that gold is neither a hedge nor a safe haven asset for stocks in BRIC markets. This result is not surprising because the accelerated financialization of commodity markets ( Huynh et al., 2020b ), including the gold market, has significantly increased investments in gold, making the gold asset behave more and more like stocks. Our findings are contrary to Wen and Cheng (2018) as they argued that safe haven properties of gold for emerging stock markets exist.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, under different returns trends of the international crude oil market, there are differences in investors' expectations and attention in the international crude oil market. Based on the above analysis, this paper defines the risks of rising and falling returns in the international crude oil market in Equations ( 4) and (5).…”
Section: Risk Measurement Methods Of International Crude Oil Marketmentioning
confidence: 99%
“…As the most financialized energy product, oil has not only commodity attributes, but also financial attributes. Global capital flows and investor speculation increase the uncertainty of risk evolution in the international crude oil market [1][2][3][4][5][6]. The evolution of crude oil risk has a significant correlation with crude oil price and returns.…”
Section: Introductionmentioning
confidence: 99%
“…Pakistan is a South Asian country with wind speed is nearly constant in certain parts of Pakistan, and the proportion of windy region is determined using the total land area. The average installed energy per square kilometer of wind power field is projected by traditional calculations to be 5 MW in order to assess the output of wind power (Duc Huynh et al 2020).…”
Section: Wind Power Potential and Energy Securitymentioning
confidence: 99%